SPECIFICITY OF POST-CONCUSSION SYMPTOMS AT 3 MONTHS AFTER MILD TRAUMATIC BRAIN INJURY. RESULTS FROM A PROSPECTIVE STUDY. (7th October 2012) - Lagarde, E; Masson, F; Ribéreau-Gayon, R; Zongo, D; Salmi, L -R; Laborey, M
Abstract : Background: Common complaints after mild traumatic brain injury (MTBI) include headaches, anxiety, irritability, and sleep disturbances, but these symptoms also occur in the non head-injured population. Whether they are more frequent among MTBI patients should help identify those that could be considered as part of the post concussion syndrome (PCS). Aims/Objectives/Purpose: We assessed the specificity of symptoms proposed in the three main scales used to measure PCS: post concussion symptoms listed in the Rivermead Post Concussion Symptoms Questionnaire (RPQ), the 4th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV), and the 10th International Classification of Diseases (ICD-10). Methods: A cohort of 536 patients with MTBI and a comparison group of 946 patients with non-head injuries were recruited in the Adult Emergency Department (ED) of a teaching hospital in Bordeaux, France. Specificity of symptoms was assessed comparing MTBI and comparison patients at 3 months taking in to account baseline levels before ED admission. Results/Outcomes: 8 symptoms were identified as being specific to MTBI: headaches, dizziness, intolerance of stress, forgetfulness, poor concentration, taking longer to think, blurred vision, and personality change. Eight symptoms were found to be not specific to MTBI: nausea, noise sensitivity, irritability, anxiety, feeling frustrated, double vision, light sensitivity and restlessness. Significance/Contribution to the Field: The relevance of symptoms proposed to constitute PCS should be reviewed. A more specific definition of PCS would make diagnosis easier and facilitate prevention as well as treatment of patients with MTBI.